Akibat Hukum Keterlambatan Pendaftaran Akta Berita Acara Rapat Umum Pemegang Saham (RUPS) Kepada Menteri Hukum dan HAM - Sugitha, Made Yoga Pramana; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
This study aims to identify and analyze the legal consequences of the deed of minutes of the general meeting of shareholders being late being registered with the Minister of Law and Human Rights and to identify and analyze efforts to delay the registration of the minutes of the general meeting of shareholders to the Minister of Law and Human Rights. The research method used in this study is a normative legal research method with a statutory approach and a conceptual approach. The results of this study explain that the legal consequences for the deed of the minutes of the general meeting of shareholders in this case related to changes to the articles of association of a Limited Liability Company are late in submitting an application for approval and notification of amendments to the articles of association to the Minister of Law and Human Rights. cannot be registered due to a delay so that the General Meeting of Shareholders becomes invalid and must be repeated. As well as efforts that can be made so that the Limited Liability Company obtains approval from the Minister of Law and Human Rights is the responsibility of the company by making a new deed, namely the deed of confirmation or deed of reaffirmation of the previous deed and the holding of the mechanism of the general meeting of shareholders again so that the deed of confirmation or a deed of reaffirmation can be made.